Padrões normativos de gênero em livros infanto-juvenis sobre educação sexual - Oliveira, Amanda Guedes de [UNESP]; Pastana, Marcela [UNESP]; Maia, Ana Cláudia Bortolozzi [UNESP] (My University, 2012)
The concept of gender is relational and refers to the the overcoming of the biological determinism, it has historical and cultural roots going beyond the anatomical differences between men and women. This documental research investigated patterns of sexuality and gender in sexual education books for children and teenagers. Ten books were analyzed, selected in bookstores websites. The content of the books and their illustrations show: 1) stereotypical and naturalized view of femininity and masculinity, 2) patterns of traditional and patriarchal families, 3) romanticized concept of marriage and reproduction, 4) stereotypes of beauty and "normal" body. It is concluded that sexual education books for children and teenagers reproduce normative standards that can stimulate a sexist education and should not be used in works of sexual education without critical reflection.

O conceito de gênero é relacional, problematiza a superação do determinismo biológico e tem raízes históricas e culturais indo além das diferenças anatômicas entre homens e mulheres. Esta pesquisa documental investigou padrões de sexualidade e gênero em livros de educação sexual infanto-juvenis. Foram analisados 10 livros, selecionados em sites de livrarias. Tanto o conteúdo dos livros como suas ilustrações mostram: 1) visão estereotipada e naturalizada da feminilidade e masculinidade, 2) padrões de famílias tradicionais e patriarcais, 3) noção romantizada de casamento e reprodução, 4) estereótipos de beleza e do corpo “normal”. Conclui-se que os livros de educação sexual infanto-juvenis reproduzem padrões normativos podendo estimular uma educação sexista não devendo ser utilizados em trabalhos de educação sexual sem reflexão crítica.
Normative standards of gender in children’s books on sexual education
Keywords: Sexuality; Gender; Sexual education; Books; Sexualidade; Gênero; Educação sexual; Livros